The changing pattern of referral in acute kidney injury. - Ali, T; Tachibana, A; Khan, I; Townend, J; Prescott, G; Smith, W; Simpson, W; Macleod, A (2011)
BACKGROUND: Acute kidney injury (AKI) is not only managed by nephrologists, but also by several other subspecialists. The referral rate to nephrologists and the factors influencing it are unknown. AIMS: To determine the referral rate, factors affecting referral and outcomes across the spectrum of AKI in a population based study. METHODS: We identified all patients with serum creatinine concentrations ≥150 µmol/l (male) or ≥130 µmol/l (female) over a 6-month period. AKI was defined according to the RIFLE classification (risk, injury, failure, loss, end stage renal disease [ESRD]). Clinical information and outcomes were obtained from each patient's case records. RESULTS: A total of 562 patients were identified as having AKI (incidence 2147 per million population/year [pmp/y]). One hundred and sixty-four patients (29%) were referred to nephrologists-referral rate 627 pmp/y. Forty-nine percent of patients whose serum creatinine rose to >300 µmol/l were referred compared with 22% in our previous study of 1997. Forty-eight patients required renal replacement therapy-incidence 184 pmp/y in comparison to 50 pmp/y in our previous study of 1997. Patients had higher odds of referral if they were male, of younger age and were in the F category of the RIFLE classification. Patients had lower odds of referral if they had multiple co-morbid conditions or if they were managed in a hospital without a nephrology service. CONCLUSION: There has been a significant rise in the referral rate of patients with AKI to nephrologists but even during our period of study only one-third of such patients were being referred. With rising incidence and increased awareness, the referral rate will certainly rise putting a significant burden on the nephrology services.